2015
DOI: 10.1111/abac.12040
|View full text |Cite
|
Sign up to set email alerts
|

Colliding Worlds: Issues Relating to Language Translation in Accounting and Some Lessons from Other Disciplines

Abstract: This paper explores implications of language translation in accounting. It draws on research on translation in other disciplines, and on insights from applied linguistics. It examines practical problems and solutions explored in other disciplines that we deem relevant to accounting. The paper also examines ideological, cultural, legal and political consequences of translation. We find that the ambiguity inherent in translation is, on the one hand, relevant for the translation of accounting principles and can c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(117 citation statements)
references
References 86 publications
6
109
0
2
Order By: Relevance
“…First, the results suggest that using translated versions of the IFRS seems to have a positive effect on decision-making. Although our results do not eradicate concerns about the inherent limitations of translation, they give reason to believe that good translations are beneficial to the application of IFRS and other international standards (see also, Evans et al, 2015). At the same time, the positive association between English language skills and decision-making quality suggests that users who are well trained in English might be able to receive equal results by using the English standard compared to using the German standard.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…First, the results suggest that using translated versions of the IFRS seems to have a positive effect on decision-making. Although our results do not eradicate concerns about the inherent limitations of translation, they give reason to believe that good translations are beneficial to the application of IFRS and other international standards (see also, Evans et al, 2015). At the same time, the positive association between English language skills and decision-making quality suggests that users who are well trained in English might be able to receive equal results by using the English standard compared to using the German standard.…”
Section: Discussionmentioning
confidence: 59%
“…However, there is also evidence for a widespread use of translated IFRS (e.g. Evans, Baskerville, & Nara, 2015), in particular in large European economies. 1 As a consequence, it is part of the reality of the use of IFRS that they are consulted by non-native English speakers in the original English version and/or in a translated version.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reputation extends to the vast literature on IFRS adoption, including its effect on issues as varied as analyst earnings forecasts (e.g. Chalmers et al, 2012;Cotter et al, 2012), language translation of international standards (Evans et al, 2015), disclosure (e.g. Crawford et al, 2014), policy choice (e.g.…”
Section: Accounting Standard Settingmentioning
confidence: 67%
“…The changes occur around the time of the informational shock, and only in countries and for firms subject to the regulatory change. Evans et al (2015) investigated the implications of language translation in accounting. They also examined the ideological, cultural, legal, and political consequences of translation and reported that the ambiguity inherent in translation was, on the one hand, relevant for the translation of accounting principles and could contribute to accounting convergence.…”
Section: Review Of the Literaturementioning
confidence: 99%